ТИЛЕЎБЕРГЕН ЖУМАМУРАТОВ ЛИРИКАСЫНДА ХАЛЫҚЛЫҚ ПАФОСТЫҢ КӨРКЕМ СӘЎЛЕЛЕНИЎИ - Жарылқасинова, М.Қ. (FAN va JAMIYAT, 2022)
The article is devoted studies the reflection of folk pathos in the work of the Karakalpak folk poet T.Jumamuratov. There have been analyzed such qualities as humanity, honesty, patriotism.